2006
DOI: 10.1128/iai.74.5.2817-2822.2006
|View full text |Cite
|
Sign up to set email alerts
|

The 6-Kilodalton Early Secreted Antigenic Target-Responsive, Asymptomatic Contacts of Tuberculosis Patients Express Elevated Levels of Interleukin-4 and Reduced Levels of Gamma Interferon

Abstract: It is well known that the majority of healthy individuals exposed to Mycobacterium tuberculosis do not become clinically ill. We have previously shown that in recently exposed healthy contacts of tuberculosis (TB) patients, a strong immune response to the M. tuberculosis 6-kDa early secreted antigenic target (ESAT-6) virulence factor correlated with a higher risk of subsequent disease, although the mechanism was unclear at that time. Inspired by recent reports that elevated expression of interleukin-4 (IL-4) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
32
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 38 publications
6
32
0
1
Order By: Relevance
“…It has been shown, in animal models, that a decreased production of IFN-c and a decrease in the number of IFN-c-producing cells are predictive of an increased risk of developing TB [40]. In contact patients, it has been observed that the progression to disease was associated with a decrease in IFN-c, and an increase in interleukin (IL)-10 and IL-4 levels [41,42]. Some data suggest that in individuals with a recent exposure to TB, the protective response shifts from Th1 to Th2, even before the clinical symptoms appear [43].…”
Section: Discussionmentioning
confidence: 97%
“…It has been shown, in animal models, that a decreased production of IFN-c and a decrease in the number of IFN-c-producing cells are predictive of an increased risk of developing TB [40]. In contact patients, it has been observed that the progression to disease was associated with a decrease in IFN-c, and an increase in interleukin (IL)-10 and IL-4 levels [41,42]. Some data suggest that in individuals with a recent exposure to TB, the protective response shifts from Th1 to Th2, even before the clinical symptoms appear [43].…”
Section: Discussionmentioning
confidence: 97%
“…on May 11, 2018 by guest http://iai.asm.org/ identify groups of individuals infected with M. tuberculosis whose elevated IL-4␦2 levels appeared to correlate with their ability to control infection (10,11). BCG vaccination-induced protection model.…”
Section: Resultsmentioning
confidence: 99%
“…Pertinently, increased levels of IL-4␦2 mRNA were recently found in people latently infected with Mycobacterium tuberculosis compared with uninfected healthy controls or patients with active pulmonary TB (10). Increased IL-4␦2 mRNA levels have also been found in TB contacts compared with noncontacts, and the authors hypothesized that the ratio of IL-4 to IL-4␦2 might be important in the progression to active disease (11,14). Lastly, chemotherapy of TB patients resulted in increased expression of IL-4␦2 in both pulmonary TB and in human immunodeficiency virus-TB coinfection (12).…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Further clinical studies have shown an association between immune reactivity to ESAT6 with that of the increased bacterial load and disease pathology in tuberculosis [29]. ESAT6 has shown to induce altered cytokine profile with decreased IFN-γ and increased IL4 responses in individuals with advanced disease [30].…”
Section: Discussionmentioning
confidence: 99%